Proceso de atención de enfermería en gestante de 35.5 semanas de gestación con hipertensión. - Suarez Moncada, Nathalie Lisbeth (2023)
Hypertensive disorders of pregnancy are among the most important that occur during pregnancy and even if left untreated, result in high morbidity and mortality for the mother and fetus. Early recognition would be the best way to deal with the case in the most conscious way, taking into account the potential adverse effect of the drugs used on the mother and its repercussions on the fetus. (Matos, 2019). Arterial hypertension that occurs after 20 weeks of gestation and recovers after delivery corresponds to the second group; It can be gestational or transient hypertension, its diagnosis should be considered when target organ damage is detected, even without proteinuria. (MSP, 2018). The present study was based on a clinical case of an 18-year-old primiparous patient with 35.5 weeks of gestation, who was referred to the Huasmo Sur General Hospital, for presenting a picture of severe preeclampsia, with blood pressure of 140/100 mmHg, headache , and photopsia. In addition to a history of preeclampsia.